Extensive Disease Changes of the Skeleton from Mediaeval Szczecin - Gładykowska-Rzeczycka, Judyta (Anthropological Review, 2022)
The changes provide an interesting example of Hyperostosis frontalis interna referred to by pathologists as the Morgagni-Stewart-Morel syndrome.